Complex SnO2 nanoparticles and nanosheets with enhanced visible-light photocatalytic activity. (April 2018) - Chang, Yu-Cheng; Lin, Jai-Cing; Chen, Ssu-Ying; Hung, Ling-Ya; Lin, Ying-Ru; Chen, Chin-Yi
Graphical abstract: Highlights: The complex SnO2 nanoparticles and nanosheets have grown by a hydrothermal method. The concentration of urea can control the morphology of SnO2 nanostructures. The complex SnO2 nanoparticles and nanosheets exhibit high photocatalytic activity. The novel structures exhibit higher photodegradation than ZnO and TiO2 nanopowders. Abstract: The complex SnO2 nanoparticles and nanosheets have been synthesized by a facile hydrothermal method. The concentrations of urea play an important role to control the morphology of SnO2 nanostructures. The complex SnO2 nanoparticles and nanosheets have excellent photocatalytic activity, which are ascribed to stronger defect emission, higher light harvesting ability in the visible light region, and higher surface-to-volume ratio, which exhibit a much better photocatalytic activity rather than commercial ZnO and TiO2 nanopowders under a blue light LED irradiation. The complex SnO2 nanoparticles and nanosheets provide a facile, low cost, high surface-to-volume ratio, high efficiency and stability visible-light-driven photocatalysts for environmental remediation and energy conversion.